1951
DOI: 10.1042/bj0480426
|View full text |Cite
|
Sign up to set email alerts
|

Selective absorption of stereo-isomers of amino-acids from loops of the small intestine of the rat

Abstract: Amino-acids may be absorbed from the small intestine in two ways, either by diffusion alone, or by a method involving an active process in one or more steps. Previous work has supported both possibilities. Hober & Hober (1937) found that the rate of entry of glycine, alanine and valine was not proportional to the concentration in the gut. They also found that these amino-acids were absorbed faster than polyhydric alcohols of comparable molecular volume and concluded that an active process was involved. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

1955
1955
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(38 citation statements)
references
References 5 publications
1
36
1
Order By: Relevance
“…The results confirmed those of Gibson & Wiseman (1951) in showing that the L-enantiomorphs of both histidine and methionine were absorbed more rapidly than the corresponding D-enantiomorphs. As Since these results were obtained Hird & Sidhu (1957) have also shown by in vivo methods the inhibition of L-histidine absorption by L-methionine, and our results are a further confirmation of the inhibition of L-histidine by L-methionine shown by Wiseman in vitro.…”
Section: Proceedings Of the Physiologicalsupporting
confidence: 80%
“…The results confirmed those of Gibson & Wiseman (1951) in showing that the L-enantiomorphs of both histidine and methionine were absorbed more rapidly than the corresponding D-enantiomorphs. As Since these results were obtained Hird & Sidhu (1957) have also shown by in vivo methods the inhibition of L-histidine absorption by L-methionine, and our results are a further confirmation of the inhibition of L-histidine by L-methionine shown by Wiseman in vitro.…”
Section: Proceedings Of the Physiologicalsupporting
confidence: 80%
“…The earliest studies in this area were conducted by Cori (19), who found that in the intact rat various sugars were absorbed at widely different rates, the order being galactose > glucose > fructose > mannose > xylose > arabinose. and histidine (23) in the small intestine. The evidence indicates that all these rapidly absorbed nutrients are taken up in the duodenum or proximal ileum, and direct measurements for some of these show that they seldom reach the distal end of the small intestine (22,24 are common in foods (25) but poorly absorbed, probably reaph the colon without attenuation in concentration.…”
Section: Absorption Patterns In the Intestinementioning
confidence: 99%
“…The transport system for D-amino acids across the intestinal membranes is the same as for L-amino acids but the L-amino acids have higher affinity (Gibson & Wiseman, 1951;Rosenhagen & Segal, 1974). D-Amino acids may be transformed to L-forms mainly in the kidney and liver (Man & Bada, 1987).…”
Section: Iii2 Absorption Distribution Excretionmentioning
confidence: 99%